Hábitos de higiene bucodental y su relación con la frecuencia de control odontológico, en los y las estudiantes de la Universidad Nacional de Loja de la modalidad de estudios presencial en el periodo mayo-julio del 2014 - Jima Narváez, Fady Vitelio (2014)
To maintain a good oral health it is indispensable to have good hygiene habits bucodental and a good control odontológico. This way, a person who has always worried about having good hygiene, about being controlled periodically with its dentist and about talking each other opportunely the problems and character illnesses odontológico, can come to major adult with its dental pieces in mouth in good condition. The realized research work was about the hygiene habits bucodental (IHO-S) and its relation with the control odontológico in and the students of the National University of Loja of the form of study presencial period In May - July, 2014” The present research work was of descriptive type, and of cross section, for which there were selected 894 students, 442 men and 452 women who were assembling the necessary characteristics to be a part of the study, a diagnosis is realized to them odontológy and the filling of the case history. The raised targets were to determine, the control frequency odontológico and the relation with hygiene habits bucodental (IHO-S), the frequency of dental brushing, to identify the implements of mouth cleaning, and the control frequency odontológico in the students of the UNL. In the National University of Loja the students presented, the hygiene habits bucodental regular (IHO-S) with (53 %), a brushing frequency of (53.35 %), the dental floss use in one (29 %), the Mouth rinsing of (33 %), and (39.14 %) visits two times the dentist. The relation of the habits of hygiene (IHO-S) with the control odontológico I can state, of the good level of the (IHO-S) there were 352 persons who represent (40 %) of which(whom) 231 persons come(turn) to the control odontológico and 3 times realize it, its percentage is of (25.83 %), on the other hand those who had a regular level of (IHO-S) were 477 persons who represent (53 %) of which 427 persons come(turn) to the control odontológico 2 times that it represents (47.76 %), which had a bad level of (IHO-S) had a frequency of 65 persons that they represent (7 %) of which 236 persons came(turned) to the control odontológico 1 time that they represent (26.39 %). Coming to the conclusion that the hygiene habits bucodental (IHOS) is not ideal although 3 times visit the dentist a year. WORDS FIX: Quality of Hygiene (IHOS), Habits of Oral Hygiene,